A study on the influence of double ellipsoidal pitting corrosion on the collapsing strength of the casing. (June 2019) - Yan, Yifei; Shao, Bing; Zhou, Xiang; Song, Shengli; Zhou, Xiaoqi; Yan, Xiangzhen
Abstract: Acid conditions in well-bore always contribute to the corrosion of casing surfaces. The local corrosion and pitting corrosion may lead to a stress concentration, decreasing the strength, which is a key factor for causing the failure of the casing. A partial model of the casing with double ellipsoidal corrosion pits is established through the FEM software ANSYS. The effects on collapsing strength of casing from the corrosion depth, cross section parameters and the distance between two pits are quantitatively analysed with the corrosion pits distributed both axially and circumferentially. The computations show the results as follows. With the increasing of the pits distance, the maximum Von Mises stress of the casing increases firstly and after the peak value, goes down to a steady state when the pits are distributed axially; however, when the pits are distributed circumferentially, the maximum Von Mises stress of casing directly goes down to a steady value. Through regression curve, it can be found that the maximum Von Mises stress of casing decreases exponentially with the increase of cross section parameters with a fixed corrosion depth. The study on the double corrosion pits for how they affect the casing's collapsing strength under varying conditions can provide a theoretical reference for the casing design. Highlights: A partial model of the casing with double ellipsoidal corrosion pits is established by FEM. Influences of parameters and distributions of the pits are studied. The terminal parameters are got according to the strength criterion.